2022
DOI: 10.1021/acs.nanolett.2c00788
|View full text |Cite
|
Sign up to set email alerts
|

Brighten Triplet Excitons of Carbon Nanodots for Multicolor Phosphorescence Films

Abstract: Triplet excitons usually do not emit light under ambient conditions due to the spin-forbidden transition rule, thus they are called dark excitons. Herein, triplet excitons in carbon nanodots (CNDs) are brightened by embedding the CNDs into poly(vinyl alcohol) (PVA) films; flexible multicolor phosphorescence films are thus demonstrated. PVA chains can isolate the CNDs, and excited state electron or energy transfer induced triplet exciton quenching is thus reduced; while the formed hydrogen bonds between the CND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 53 publications
1
54
0
Order By: Relevance
“…Note that no afterglow emission could be detected at room temperature through embedding seed‐CDs into matrices (e.g., polyvinyl alcohol (PVA), Figure S13, Supporting information) that commonly being used to modify CDs, indicating that only hydrogen bonding fixation is not sufficient to activate RTP of seed‐CDs. [ 24,48 ] Besides that, as shown in Figure S14, Supporting Information), it can be found that the urea molecule has no direct effect on the surface states of CDs because no phosphorescence was observed from the physical blends of the seed‐CDs and urea. There is also no phosphorescence can be observed from B‐CDs 80 300 , and the XRD pattern of B‐CDs 80 300 is also almost the same as u‐seed‐CDs (Figures S15 and S16, Supporting Information).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Note that no afterglow emission could be detected at room temperature through embedding seed‐CDs into matrices (e.g., polyvinyl alcohol (PVA), Figure S13, Supporting information) that commonly being used to modify CDs, indicating that only hydrogen bonding fixation is not sufficient to activate RTP of seed‐CDs. [ 24,48 ] Besides that, as shown in Figure S14, Supporting Information), it can be found that the urea molecule has no direct effect on the surface states of CDs because no phosphorescence was observed from the physical blends of the seed‐CDs and urea. There is also no phosphorescence can be observed from B‐CDs 80 300 , and the XRD pattern of B‐CDs 80 300 is also almost the same as u‐seed‐CDs (Figures S15 and S16, Supporting Information).…”
Section: Resultsmentioning
confidence: 95%
“…And the SiO 2 in the matrix could effectively form hydrogen bonds with these groups, being expected to reduce their vibration‐induced non‐radiative transition, which can be verified by the blueshift of OH related vibration peak from 3370 to 3429 cm −1 and more thermogravimetric loss for the B‐CDs 300 sample when compared with the seed‐CDs (Figure S9, Supporting information). [ 48 ] In addition, it is also intriguing to observe that the stretching vibration intensity of CO at 1609 cm −1 increases obviously from seed‐CDs to B‐CDs 300 sample, and an additional vibration peaked at 1662 cm −1 assigned to the stretching vibration of CN in CNH groups can be also observed in B‐CDs 300 , indicating that more CO and CN bands have been formed on the surface of B‐CDs 300 . [ 40,49 ]…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in this work, integrating CDs@zeolite composites and PeQDs into a container to shorten the radiation distance between energy donors and energy acceptors is a facile approach to achieving efficient RET. According to a reported equation, [ 42 ] based on the afterglow lifetimes of CDs@zeolite‐2 and Orange/Red‐PeQDs, the PLQY of Orange/Red‐PeQDs (Table S1, Supporting Information), as well as the afterglow QY of CDs@zeolite‐2 (6.2%), the afterglow QY of Orange/Red‐PeQDs are calculated to be 4.3% and 5.5%, respectively. Detailed computing methods and discussions are shown in Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…These groups featuring n –π* transition absorption and emission characteristics are formed by the reaction between/among precursors, carbonization at high temperatures, and/or oxidation by water or oxidants. When they anchored on the surface of the C-dots, various matrices were required to immobilize the external n –π* emissive center for activating RTP. Reversely, if these groups were embedded in the interior of C-dots, the internal hydrogen bonds and polymer-like covalent bonds of C-dots as self-matrices can “lock” the internal triplet excitons, efficiently suppressing the nonradiative relaxation. Therefore, long-lived afterglows in the exterior and interior of the C-dots were observed. Two types of matrix-free RTPs of the C-dots were fabricated due to the low energy gap between S 1 and T 1 (Δ E ST ) , and heavy atom effect. Unfortunately, many C-dots-based RTPs can be observed in the solid state because these C-dots are highly hydrophilic and easily infiltrated by water containing dissolved oxygen, resulting in the insufficiency of RTP in aqueous solution .…”
Section: Introductionmentioning
confidence: 99%